ANALYSIS OF PATIENT SATISFACTION WITH INPATIENT SERVICES IN REGIONAL GENERAL HOSPITALS - Tri Sulistyowati, Wiwin; Lilis Suryani; Ali Harokan (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
Patient satisfaction is a measure of the extent to which patients are satisfied with the health care they receive from health service providers. This study aims to determine factors related to patient satisfaction with inpatient services at Regional General Hospitals in 2024. The design of this research is quantitative with a cross-sectional approach. The population in this study were inpatient patients at the Regional General Hospital in 2023. The sample in this study was 94 people. The sampling method uses purposive sampling. This research was carried out on February 12 - March 16 2024.  Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. The results of the research show that there is a relationship between tangible (p value 0.001), reliability (p value 0.000), responsiveness (p value 0.001), assurance (p value 0.007) and empathy (p value 0.000) on patient satisfaction with inpatient services at Regional General Hospitals in 2024 The most dominant factor in patient satisfaction with regional general hospital inpatient services in 2024 is empathy (p value 0.000) (OR .125). The conclusion is that there is a relationship between tangible, reliability, responsiveness, assurance and empathy on patient satisfaction with inpatient services at Regional General Hospitals in 2024. Hospitals should provide services in inpatient rooms, provide fast and responsive service in responding to complaints from patients.